The Influence of the Tagline Free Shipping and E-Service Quality on Shopee Market Place Purchasing Decisions Among FEB UGJ Cirebon Students - Ghina Cahyani; Putri Kinanti; Intan Van Dhiny; May Dedu (PT FORMOSA CENDEKIA GLOBAL, 2024)
Shopee is an Indonesian online marketplace that facilitates buying and selling. Web apps serve as its foundation. Several marketplaces compete with Shopee. The goal of this study is to determine how free shipping deals and the caliber of e-services affect the judgments made by FEB UGJ Cirebon students about the Shopee marketplace. In this study, a quantitative research methodology was utilized. The research population consists of the FEB UGJ Cirebon students who use Shopee. 142 respondents make up the sample size used in this purposive sampling technique. The SPSS program, version 22, is used in the analytical approach. Purchase decisions made by customers are known to be positively and significantly impacted by the slogan